Molecular and phenotypic characterization of pathogenic fungal strains isolated from ginseng root rot. (December 2018) - Durairaj, Kaliannan; Velmurugan, Palanivel; Vedhanayakisri, Kaliyappan Amballandi; Chang, Woo-Suk; Senthilkumar, Palaninaicker; Choi, Kyung-Min; Lee, Jeong-Ho; Oh, Byung-Taek
Abstract: In the present study, we investigated the diversity of pathogenic fungal strain isolated from infected Korean ginseng root rot and tested their morphology, molecular characterization, and pathogenic impact. From the results, we have identified different shapes of fungal conidia such as cylindrical, conical, bell and convex shape. The molecular identification of fungal strains was characterized based on partial ITS sequence analysis and it was published in National Center for Biotechnology Information (NCBI). Among them totally eleven strains, eight were pathogens, and three were endophytic strains. Our conclusions suggest that pathogenic fungi have different communities and structures than non-pathogenic fungi. Graphical abstract: Image 1 Highlights: Eleven different pathogenic fungi species have been screened from the ginseng root rot. The isolate have been characterized by molecular approach and sequence were submitted in NCBI. Among eight stains have higher pathogenic impact.